Simulation and Modeling of a AC-DC Converter Controlled by Pulse Width Modulation Using Soft Switching topology - A. hanoon, Hasanain (University of Thi-Qar Journal of Science, 2012)
This work presents the design, analysis, and simulation of AC-DC converter topology incorporating a voltage source converter (VSC) and a direct converter, connected with medium frequency transformer isolation. A control method is studied by which it is possible to reduce the transformer core losses by only magnetizing the transformer when a Pulse Width Modulation (PWM) pulse should be applied on the AC side of the system. By alternately commutating the two converters it is possible to achieve soft switching conditions for all of the semiconductor elements. Furthermore, it is shown that resonant commutation of the voltage source converter is possible by utilizing the cycloconverter for short circuiting the transformer terminals. converter. The PWM voltage is applied to aninductive filter and thereby the AC side current aswell as the power flow through the system can be